Handwriting fluency and the quality of primary grade students’ writing - Skar, Gustaf B.; Lei, Pui-Wa; Graham, Steve; Aasen, Arne Johannes; Johansen, Marita Byberg; Kvistad, Anne Holten (Reading & writing, 2022)
Until children can produce letters quickly and accurately, it is assumed that handwriting disrupts and limits the quality of their text. This investigation is the largest study to date (2596 girls, 2354 boys) assessing the association between handwriting fluency and writing quality. We tested whether handwriting fluency made a statistically unique contribution to predicting primary grade students’ writing quality on a functional writing task, after variance due to attitude towards writing, students’ language background (L1, L2, bilingual), gender, grade, and nesting due to class and school were first controlled. Handwriting fluency accounted for a statistically significant 7.4% of the variance in the writing quality of primary grade students. In addition, attitude towards writing, language background, grade and gender each uniquely predicted writing quality. Finally, handwriting fluency increased from one grade to the next, girls had faster handwriting than boys, and gender differences increased across grades. An identical pattern of results were observed for writing quality. Directions for future research and writing practices are discussed.